Development of PPKn worksheet using problem-based learning to improve critical thinking - Jesika Sitorus; Dede Ruslan; Rosmala Dewi (Himpunan Pengembang Kurikulum Indonesia, 2025)
The need for learning that is able to improve critical thinking skills, active participation of students, and suitability for children's cognitive development. This research aims to develop Problem-Based Learning (PBL) based Pancasila Education (Pendidikan Pancasila dan Kewarganegaraan or PPKn) student worksheets (Lembar Kerja Peserta Didik or LKPD) on the material “Aku Patuh Aturan” for grade III students of SDN 101912 Pagar Merbau. This research uses a modified ADDIE development model, including the stages of analysis, design, development, implementation, and evaluation. The instruments used were validation sheets, response questionnaires, and multiple-choice patterned pre-test-post-test tests. Data analysis was carried out descriptively and quantitatively using percentages for feasibility and practicality and comparative analysis for effectiveness. The validation results showed that the LKPD was very valid from the aspects of material, media, and language. Practicality tests on a small group and field trials resulted in a very practical category based on teacher and student responses. The effectiveness evaluation revealed a significant increase in students' critical thinking skills, with the percentage of completed students increasing from 4.5% to 81.8%. These findings strengthen the conclusion that PBL-based LKPD is feasible to use and effective in improving critical thinking of elementary school students. Abstrak Kebutuhan pembelajaran yang mampu meningkatkan keterampilan berpikir kritis, partisipasi aktif murid, dan kesesuaian dengan perkembangan kognitif anak. Penelitian ini bertujuan mengembangkan Lembar Kerja Peserta Didik (LKPD) Pendidikan Pancasila berbasis Problem-Based Learning (PBL) pada materi “Aku Patuh Aturan” untuk murid kelas III SDN 101912 Pagar Merbau. Penelitian ini menggunakan model pengembangan ADDIE yang dimodifikasi meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Instrumen yang digunakan berupa lembar validasi, angket respons, dan tes pre-test-post-test berpola pilihan ganda. Analisis data dilakukan secara deskriptif kuantitatif menggunakan persentase untuk kelayakan dan kepraktisan serta analisis perbandingan untuk efektivitas. Hasil validasi menunjukkan LKPD sangat valid dari aspek materi, media, dan bahasa. Uji kepraktisan pada uji coba kelompok kecil dan lapangan menghasilkan kategori sangat praktis berdasarkan respons guru dan murid. Evaluasi efektivitas mengungkapkan peningkatan signifikan keterampilan berpikir kritis murid, dengan persentase murid tuntas bertambah dari 4,5 % menjadi 81,8 %. Temuan ini memperkuat kesimpulan bahwa LKPD berbasis PBL layak digunakan dan efektif dalam meningkatkan berpikir kritis murid sekolah dasar. Kata Kunci: berpikir kritis; lembar kerja peserta didik; LKPD; pendidikan Pancasila; problem-based learning